The mythical notion of justice in Euripides and Plato - Torrano, Jaa (Revista Archai, 2025)
The mythical notion of justice collides with difficulties and misunderstandings, but it can be rescued by examining the features of mythical thought and its internal coherence as documented in Hesiod’s Theogony. In Euripides’ theater, the notion of justice is thought and determined within a traditional repertoire of images and notions documented in Hesiod’s Theogony. In Plato’s Dialogues, the philosophical notion of justice shows features shared by paradigmatic mythical notion of justice and these shared features draw the structural homo-logy between the mythical and philosophical notions of justice.